Perceptions of Pre-Service Teachers of Mathematics on Peer-Feedback in Classroom Learning - Noor, Siti Jamilah; Rahmatika, Noor Baiti; Lissa, Juhairiah (SMARTH: Journal of Mathematics Education and Learning, 2025)
Mathematics learning in higher education increasingly demands active, collaborative, and self-regulated learning; however, classroom practices often remain lecturer-centered, limiting students’ opportunities to reflect on their understanding and engage meaningfully with peers. Peer feedback is a collaborative instructional strategy with strong potential to address this gap by promoting dialogue, reflection, and shared knowledge construction. This study investigates pre-service teachers’ perceptions of peer feedback in mathematics learning, focusing on its contributions to conceptual understanding, engagement, motivation, collaboration, and self-regulated learning. A quantitative descriptive design was employed involving 20 pre-service teachers who participated in structured peer feedback activities over one academic semester. Data were collected using a 35-item Likert-scale questionnaire and analyzed through descriptive statistics, including mean scores and frequency distributions. The results indicate consistently positive perceptions across all indicators, with mean scores ranging from 3.30 to 3.50. Participants reported that peer feedback helped clarify mathematical concepts, deepen conceptual understanding, increase learning motivation and engagement, encourage collaborative interaction, and support reflective thinking. These findings suggest that well-structured peer feedback functions as an effective pedagogical complement to lecturer instruction, offering cognitive, motivational, and social benefits. Integrating peer feedback into mathematics classrooms can strengthen interactive learning environments and support the development of reflective, autonomous, and self-regulated future mathematics teachers.